P-140 'Local people helping local people': a teenager's contribution to dementia friendly sway. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Russell, Sophie; Tarling, Stephen; Willis, Fiona; Russell, Sarah
Abstract : Background: In the UK there are around 800, 000 people with dementia. Dementia friendly communities are places where more people understand dementia and people are supported to live well. Sway is a small village in the New Forest (population 3548). One of Sway Parish Council's strategic objectives is to help ageing people live well. As a carer and as part of her Duke of Edinburgh Bronze Award this abstract describes a 15-year-old's activity in supporting the parish council's strategic objective. Aims: To support people with dementia and their carers: ' Local People Helping Local People' To connect and collaborate with other local groups: 'Helping People Live Well'. Method: Dementia Friends sessions to parish council, girl guide groups, churches, interest groups, care homes and agencies as well as businesses (e.g. hairdresser, gardeners, and postmen) Role-modelling dementia friendly attitudes and behaviour (e.g. there is more to a person than dementia) in village activities, Saturday job in local coffee shop and monthly dementia friendly coffee and chat group Information animations to raise awareness Providing a teenager's perspective to local volunteer action group. Results: As part of Hampshire's Dementia Friendly Communities initiative and Sway parish council's objectives; business in Sway are becoming officially Dementia Friendly through attendance at Dementia Friends sessions and always having a dementia friendly helper on duty. There is partnership working between the parish council, other local charities, volunteer groups and the dementia action group. Conclusion: Dementia is a progressive terminal disease which benefits from a palliative care approach at all stages. Palliative care does not only have to be provided by health services or by adults. It can also be delivered by neighbours and community partners of all ages. Harnessing the experiences and passion of a community including teenagers (with school or vocational curriculums to meet) has the potential to support Dementia Friendly Communities where people live and die well with dementia.